EKSPLORASI PENGGUNAAN APLIKASI KEUANGAN BERBASIS ANDROID DALAM PENGELOLAAN KEUANGAN RUMAH TANGGA - Ruci, Dewa; Prasetyo, Henri (Komunitas Manajemen Kompetitif, 2025)
This research explores the use of Android-based financial applications in household financial management in Pontianak, West Kalimantan. Employing a qualitative case study approach, the study aims to analyze the motivations, process of use, utilized features, and the impact of these applications on the family's financial behavior and decisions, including their adaptation to changing income conditions. Data were collected through in-depth interviews with Mrs. Masithah, who is responsible for managing the household's finances. The findings indicate that the digital financial application was adopted as a response to the difficulty of managing low income. The choice of application was based on its ease of use, the completeness of its reporting features, and its free availability. Disciplined usage, even for small transactions, enabled the maintenance of financial categories, goal-directed expenditure, and improved investment and health planning. Interestingly, these applications not only provided assistance during difficult times but also became a “lifestyle necessity” as the household's income increased. This finding suggests that digital financial applications play a significant role in enhancing financial literacy at the household level and fostering proactive financial behavior, while also facilitating family financial transparency and collaboration. This study contributes to the understanding of the dynamics of financial technology adoption at a micro-level and its implications for household well-being.